2020
DOI: 10.1108/jaee-12-2019-0231
|View full text |Cite
|
Sign up to set email alerts
|

The effect of board multiple directorships and CEO characteristics on firm performance: evidence from Palestine

Abstract: PurposeThe purpose of this study is to empirically examine the effect of board multiple directorships and chief executive officer (CEO) characteristics on firm performance among nonfinancial firms listed on the Palestine Security Exchange (PSE) during the period from 2009 to 2016.Design/methodology/approachBased on 200 observations, this study utilizes panel data to examine the effect of the predictors on firm performance measured by return on assets. The analysis is repeated using the return on equity and two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
1
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 57 publications
2
35
1
6
Order By: Relevance
“…Generally, a change in the leadership structure from CEO duality to non-duality improves (Yasser et al, 2015): duality means that the Chairman is also the CEO of the firm, and non-duality that the posts are held by different individuals (Lam & Lee, 2008). In addition, previous studies claim that the separation of these positions, and an older CEO with long tenure, are positive attributes enhancing operating performance (Dogan et al, 2013;Peni, 2014;Saleh et al, 2020). Consistently, the negative association between CEO duality and firm performance supports the agency theory assumption (Dogan et al, 2013).…”
Section: Introductionmentioning
confidence: 60%
See 3 more Smart Citations
“…Generally, a change in the leadership structure from CEO duality to non-duality improves (Yasser et al, 2015): duality means that the Chairman is also the CEO of the firm, and non-duality that the posts are held by different individuals (Lam & Lee, 2008). In addition, previous studies claim that the separation of these positions, and an older CEO with long tenure, are positive attributes enhancing operating performance (Dogan et al, 2013;Peni, 2014;Saleh et al, 2020). Consistently, the negative association between CEO duality and firm performance supports the agency theory assumption (Dogan et al, 2013).…”
Section: Introductionmentioning
confidence: 60%
“…According to Antia et al (2010), greater agency cost, lower company value and higher levels of knowledge risk are correlated with a shorter CEO horizon. The longer the term of the CEO, the higher is the performance of the firm, because long-serving CEOs can become specialists in all facets of the firm's activities and technicalities (Saleh et al, 2020). Thus, from the findings of the previous studies, CEO effectiveness (non-duality, age, and tenure) influences operating performance.…”
Section: Ceo Effectiveness Chairman and Operating Performancementioning
confidence: 98%
See 2 more Smart Citations
“…Correlation analysis was conducted to identify the relationship between the key factors related to Information Technology, and their relationship with the economic development of manufacturing's firms. The results have been presented [17]. When the IT Valence (ITV) was investigated for its relationship with other variables, it was found that ITV had moderate relationship with RE (0.671) and ED(0.623), but weak relationship with ME (0.564) and ITC (0.487).…”
Section: Hypothesis Testingmentioning
confidence: 98%